Pengaruh Indikator Rasio Keuangan Perusahaan Price Earning Ratio (PER) dan Price to Book Value (PBV) terhadap Return Portfolio Saham di Bursa Efek Jakarta - Gunawan, Barbara; Budileksmana, Antariksa (Journal of Accounting and Investment, 2003)
This emerged during a kind of perception that the financial statements do not quite believable as the basis of capital market investment decisions. Using the results of the ratio of the financial statements as an object to be examined, the study will look at the extent of the influence indicator Price Earning Ratio and Price to Book Value of the Return Portfolio Shares on the Jakarta Stock Exchange. The results showed that of the portfolio is formed, it turns out the low indicators of Price Earning Ratio and Price to Book Value does not affect the portfolio return.